2018
DOI: 10.1017/s0025315418000462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanized dredging targeting Chamelea gallina, striped venus clams, on the associated discards in the northern Alboran Sea (Western Mediterranean Sea)

Abstract: Mechanized dredging impact on discards was assessed along the northern Alboran Sea (W Mediterranean Sea). Data from 101 dredging operations were analysed for contrasting spatial and seasonal variability of damage, with the use of a three-level damage scale. 4.5% of discarded individuals displayed intermediate damage, whereas 11.3% displayed severe damage. Echinoderms displayed the highest level of damage (~75% of total collected individuals) and Echinocardium cf. mediterraneum was the most susceptible discarde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The results of this study showed that mechanized clam dredging causes considerably greater damage and mortality to the benthic megafauna of the trunculus (Urra et al, 2017;Urra et al, 2019). These notable differences between areas may be the result of: (1) different levels of fishing disturbance (intensity and frequency of the fishing activity); (2) the effect of the Maresme fishing closure in the abundance and diversity of benthic species (e.g., the increase of species with fragile shells); (3) Different local environmental conditions (e.g., depth, sediment grain size) or anthropogenic activities.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The results of this study showed that mechanized clam dredging causes considerably greater damage and mortality to the benthic megafauna of the trunculus (Urra et al, 2017;Urra et al, 2019). These notable differences between areas may be the result of: (1) different levels of fishing disturbance (intensity and frequency of the fishing activity); (2) the effect of the Maresme fishing closure in the abundance and diversity of benthic species (e.g., the increase of species with fragile shells); (3) Different local environmental conditions (e.g., depth, sediment grain size) or anthropogenic activities.…”
Section: Discussionmentioning
confidence: 74%
“…Clam dredging has been described to be among those practices with the greatest impact on coastal benthic ecosystems (Collie et al, 2000). The impact of mechanized clam dredging on benthic communities inhabiting fine sands has been detailed for the striped venus clam (Chamelea gallina) and the wedge clam (Donax trunculus) fisheries in Andalusia (Urra et al, 2017;Urra et al, 2019) and Catalonia (Baeta et al, 2021a) (both in the western Mediterranean Sea). The effect of similar fishing gears was also described for the smooth clam (Callista chione) and the surf clam (Spisula solida) in southern Portugal (Gaspar et al, 2001;.…”
Section: Introductionmentioning
confidence: 99%